Evaluasi Keamanan Sistem Informasi Pada SMKN 1 Banyumas Berdasarkan Indeks Keamanan Informasi (KAMI) ISO 27001:2013 - Rizki Nugroho; Ito Setiawan; Rafii Nur Akmal; Najmul Azka (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the era of globalization, schools are required to be able to adapt to the rapid development of technology. One important aspect that needs to be considered is school data management. A good information system is not only able to manage student attendance data and book inventory, but can also help in making more effective decisions. SMK Negeri 1 Banyumas, which is the focus of this research, is expected to be an example of how a school can utilize information technology to improve the quality of its services